CASSAVA PRODUCTS VALUE CHAIN ANALYSIS AMONG ACTORS’ PROCESSORS UNDER TRADITIONAL AND IMPROVED TECHNOLOGIES IN NASARAWA STATE, NIGERIA - Oladele A.O.; Alabi O.O.; Maharazu I. (Russian Journal of Agricultural and Socio-Economic Sciences, 2020)
This study examined cassava products value chain analysis among actors’ processors under traditional and improved technologies in Nasarawa State, Nigeria. Specifically, the study was designed to achieve the following objectives: determine the socio-economic characteristics of cassava processors, analyze the costs and returns of actors processing cassava into chips and garri, determine the mean rating of traditional and improved technologies utilized by actors, evaluate factors influencing output of cassava processing into chips, and garri by actors, and determine the constraints or problems facing actors or processors in the activities of processing cassava into chips, and garri. The study employed multi-stage sampling design. Total 100 actors’ processors engaging in cassava processing activities were sampled and utilized .Primary data were utilized using well-designed, structured questionnaire. The statistical and econometric tools employed were, descriptive statistics, gross margin model, financial analysis, net income analysis, five point Likert scale, Probit Model analysis, and principal component analysis (PCA).The results show that 92% of actors in cassava processing activities were between 21 to 50 years of age. The mean age of actors was 41 years. About 82% of actors had formal education. The mean household size was 9 people. Also, 47% of actors had less than 20 years experiences in cassava processing activities. The calculated net returns for garri enterprise were 42,000 Naira. The net returns for cassava chips enterprise were calculated to be 20,550 Naira. The gross margin ratios for garri and cassava chips were 0.57 and 0.49 respectively. This means that for every one (1) Naira invested in garri and cassava chips enterprises, 57 kobo and 49 kobo covered expenses, taxes, profits, and depreciation for garri and cassava chips enterprises respectively. The major traditional technologies used by actors were: local bag (jute) for bagging cassava products, hand grating for peeling cassava, and calabash bowl used for washing cassava products. The improved or modern technologies used by actors include: mechanical pulverizer, solar drier for drying cassava products, kiln or oven for drying cassava products, motorized grater for grating cassava, and mechanical peeler. The statistical significant variables influencing output of cassava processing by actors include: gender (P<0.05), marital status (P < 0.01), experience in cassava processing (P < 0.01), level of education (P < 0.01), contact with extension agents (P < 0.01), and distant to nearby market (P < 0.01). The major constrains or problems facing actors in cassava processing activities were; high cost of processing inputs, high cost of transportation, shortage of hired labour, lack of access to credit facilities amongst others. The retained variables explained 98.61% of the variations included in the model. The study recommends that extension agents should be employed to disseminate research findings on improved or modern processing technologies to actors, also government should formulate policies to stabilize prices for agricultural commodities, actors should also form cooperative organizations to access credit facilities and modern processing equipments.